PECULIARITIES OF POSTOPERATIVE PAIN IN THE ELDERLY AND SENILE PATIENTS AT DIFFERENT STAGES OF NOCICEPTION - V.O. Telegan; K.V. Tarasenko (Проблеми екології та медицини)
According to modern concepts, the process of nociception includes transduction, transmission, modulation, and perception. However, at this stage of the development of modern medicine, not enough studies have been devoted to the issue of specific clinical and laboratory indicators of different stages of nociception in the elderly and older age, which may be related to both the aging process of the causes and the consequences of concomitant pathology. Therefore, the aim of our study was to evaluate the peculiarities of the state of the nociceptive system at the stages of transmission, modulation, and perception in older, elderly, and young people. We conducted a clinical study, which was organized based on the communal enterprise "3rd City Clinical Hospital of the Poltava City Council" in 2018-2020. The study included 201 patients who were in the postoperative period, regardless of the type of intervention and nosology. All examined patients were divided into 3 groups according to age: group 1 (n=82) – elderly people, group 2 (n=21) – older people, and control group (n=98) – young people. The study of neurophysiological indicators of the conductivity of sensory fibers was carried out by measuring the speed of propagation of the nerve impulse along the sensory fibers of the lower and upper extremities using stimulation electroneuromyography. The nociceptive flexor reflex was measured to assess the stage of modulation of nociception. We recorded the reflex threshold and the subjective pain threshold, as well as their content. To objectify the strength of the pain sensation, pressor algometry was used, which took place several times in the measurement of the subjective assessment of pain, with the appearance of painful stimuli increasing in intensity. We did not find any statistically significant differences in the sensory speed of recovery along fibers n. ulnaris and n. medianus between the right and left sides, as well as between patients of different groups in the early postoperative period. There are no age differences in the stage of pain impulse transmission in the upper limbs in the early postoperative period. However, a statistical value was established below the speed of recovery by sensory fibers of the lower extremities in the early postoperative period, in particular by n.peroneus superficialis and n. suralis, in the elderly. The ratio of the pain threshold to the reflex threshold showed differences in all groups. The higher threshold in the private control group was higher than group 2 and did not differ from group 1. A statistically lower pain tolerance was noted in groups 1 and 2 relative to the control group, but no difference was found between the elderly and older age groups. Thus, it was found that elderly patients have differences in various stages of nociception, in particular, transmission, modulation, and perception, which complicates the treatment of pain syndrome in the postoperative period and requires further research with further development of ways to optimize therapeutic tactics.